Mutation mapping of a variegated EMS tomato reveals an FtsH-like protein precursor potentially causing patches of four phenotype classes in the leaves with distinctive internal morphology - Punyavee Dechkrong; Sornsawan Srima; Siriphan Sukkhaeng; Winai Utkhao; Piyanan Thanomchat; Hans de Jong; Pumipat Tongyoo (BMC Plant Biology, 2024)
Abstract Background Leaf variegation is an intriguing phenomenon observed in many plant species. However, questions remain on its mechanisms causing patterns of different colours. In this study, we describe a tomato plant detected in an M2 population of EMS mutagenised seeds, showing variegated leaves with sectors of dark green (DG), medium green (MG), light green (LG) hues, and white (WH). Cells and tissues of these classes, along with wild-type tomato plants, were studied by light, fluorescence, and transmission electron microscopy. We also measured chlorophyll a/b and carotene and quantified the variegation patterns with a machine-learning image analysis tool. We compared the genomes of pooled plants with wild-type-like and mutant phenotypes in a segregating F2 population to reveal candidate genes responsible for the variegation. Results A genetic test demonstrated a recessive nuclear mutation caused the variegated phenotype. Cross-sections displayed distinct anatomy of four-leaf phenotypes, suggesting a stepwise mesophyll degradation. DG sectors showed large spongy layers, MG presented intercellular spaces in palisade layers, and LG displayed deformed palisade cells. Electron photomicrographs of those mesophyll cells demonstrated a gradual breakdown of the chloroplasts. Chlorophyll a/b and carotene were proportionally reduced in the sectors with reduced green pigments, whereas white sectors have hardly any of these pigments. The colour segmentation system based on machine-learning image analysis was able to convert leaf variegation patterns into binary images for quantitative measurements. The bulk segregant analysis of pooled wild-type-like and variegated progeny enabled the identification of SNP and InDels via bioinformatic analysis. The mutation mapping bioinformatic pipeline revealed a region with three candidate genes in chromosome 4, of which the FtsH-like protein precursor (LOC100037730) carries an SNP that we consider the causal variegated phenotype mutation. Phylogenetic analysis shows the candidate is evolutionary closest to the Arabidopsis VAR1. The synonymous mutation created by the SNP generated a miRNA binding site, potentially disrupting the photoprotection mechanism and thylakoid development, resulting in leaf variegation. Conclusion We described the histology, anatomy, physiology, and image analysis of four classes of cell layers and chloroplast degradation in a tomato plant with a variegated phenotype. The genomics and bioinformatics pipeline revealed a VAR1-related FtsH mutant, the first of its kind in tomato variegation phenotypes. The miRNA binding site of the mutated SNP opens the way to future studies on its epigenetic mechanism underlying the variegation.